The Concept of Multicultural Education in Al-Qur’an Surah Al-Hujarat Verse 11-13 - S, Muhammad Tang; Muslimah, Muslimah; Riadi, Akhmad (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Many normative basis on multiculturalism exist in the Holy Book of Qor’an. Islamic multicultural education is a solution to the problem of intolerance behavior towards human diversity. This study is discussed the concept of multicultural Islamic education in Surah Al-Hujurat verses 11, 12 and 13 based on both perspective of interpretation of Ibn Kathir's and Al-Misbah's. This study is library study through a thematic approach. The primary data taken from the interpretation of Ibnu Katsir and the interpretation of Al-Misbah. Furthermore, the secondary data were obtained from relevant books and articles. Data were collected through the documentation by collecting, classifying, quoting, checking data related to the study. The instrument of this study is the researcher himself, who acts as a planner, executor, collector, analyzer, and interpreter of the data. Data were analyzed using content analysis methods (hermeneutic interpretation) and maudhu’ i method. There are three fundamental concepts of Islamic multicultural education contained in the Al-Quran surah Al-Hujurat verses 11-13. The first is to avoid mocking and insulting other people, Secondly, keep away from prejudice and gossipping others, and Thirdly, getting to know each other comes from different tribes, customs, languages, cultures, groups, social status, and even religions by always promoting mutual respect and understanding.